Factors Affecting Depth of Penetration in Microneedling- and Laser-Assisted Drug Delivery: The Importance of Timing of Topical Application. Issue 12 (December 2020) - Chung, Hye Jin; Cheng, Judy; Gonzalez, Manuel; Al-Janahi, Sara
Abstract : BACKGROUND: Microneedling- and laser-assisted drug delivery are emerging techniques used to treat various conditions. However, key parameters affecting drug penetration remain unknown. OBJECTIVE: This study aims to investigate the importance of timing of topical application, needle length, and device type for drug delivery. MATERIALS AND METHODS: Skin harvested from cosmetic surgeries was treated with black ink applied before or after treatment with a microneedling pen (MP), roller, or fractional ablative CO2 laser, and incubated for different time intervals. Ink penetration was additionally tested using different needle lengths. Sandwich estimator was used for statistical analysis. RESULTS: Ink applied before MP penetrated deeper compared to ink applied afterward at 1 and 3 hours, and roller microneedling in both the ink-before and -after scenarios at 1, 3, and 6 hours ( p < .05). Microneedling demonstrated lateral extension of ink beyond microchannels with increased ink penetration over time. CO2 laser demonstrated ink localization within microthermal zones without time-dependent increases in depth after 30 minutes. Ink penetration increases by 0.06 mm per 1 mm increase in needle length. CONCLUSION: Ink applied before MP results in the deepest penetration of ink. Microneedling offers unique advantages in transdermal delivery as its channels exhibit increasing penetration over time and lateral extension of product. Abstract : Supplemental Digital Content is Available in the Text.